A COMPARATIVE STUDY ON THE EFFECT OF COOPERATIVE LEARNING TECHNIQUES (NHT & TPS) ON STUDENTSâ READING COMPREHENSION VIEWED FROM DIFFERENT TEXT TYPES - Desi, NyomanAyu Sri; Nitiasih, Kerti; Luh Putu, Artini, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract The present study aimed at comparing the effect of two cooperative learning techniques, namely, Numbered Heads Together (NHT) and Think-Pair-Share (TPS) viewed from different text types (narrative, spoof, and hortatory exposition) on studentsâ reading comprehension. The research design used in this study was Post-test Only Comparison Group Design. The samples were two classes of the eleventh grade students at SMA Negeri 2 Singaraja. After the treatment sessions, post-test was administered to obtain the data. The data obtained from the post-test were analyzed by using descriptive and inferential statistical analyses. From the analyses, it was found that there was a significant difference between the effect of those techniques. There was an interaction between the techniques and the text types. NHT affected better than TPS although in spoof and hortatory exposition texts the differences were not significant. This study has the implication to EFL pedagogy especially in the teaching of reading skill. Â Key Words:Reading Comprehension, Numbered Heads Together (NHT), Think-Pair-Share (TPS), Text Types Â